Altered Regional Homogeneity in Patients With Diabetic Erectile Dysfunction: A Resting-State fMRI Study - Chen, Jianhuai; Huang, Xinfei; Tang, Qinglai; Xiang, Ziliang; Xu, Yan; Liu, Tao; Yang, Zhaoxu; Yang, Jie; Chen, Yun (Frontiers in Endocrinology, 2022)
Introduction Erectile dysfunction (ED) is a common complication of Type-2 Diabetes Mellitus (T2DM) for male patients and it is considered to be associated with different causes including hyperglicemia-induced vascular endothelial cell damages. However, the possible central neural mechanisms shared by these two diseases remain unclear. This study aimed to explore the changes of brain activity and their relationships with the clinical characteristics in patients with diabetic ED. Methods The data of resting-state functional magnetic resonance imaging were acquired in 31 T2DM patients with ED (DM-ED) and 31 matched healthy controls (HCs). The whole-brain regional homogeneity (ReHo) values were calculated and compared between groups. In addition, Pearson correlation analysis was performed to evaluate the relationships between brain regions with altered ReHo values and clinical characteristics in the patient group. Results The DM-ED group exhibited increased ReHo values in the right middle frontal gyrus (orbital part) and decreased ReHo values in the left superior frontal gyrus (dorsolateral), paracentral lobule, precuneus and bilateral supplementary motor area when compared with the HCs group. Moreover, significantly negative correlations were found between ReHo values of the left superior frontal gyrus (dorsolateral) and IIEF-5 scores, as well as the level of HbA1c in the DM-ED group. Conclusion The altered spontaneous brain activity in cognitive-related regions revealed by ReHo values might provide new insights into the neurological pathophysiology underlying DM-ED and serve as potential neuroimaging biomarkers for detecting and evaluating ED in diabetes patients.